PEMAHAMAN MENDALAM TENTANG EKOSISTEM UNTUK SISWA KELAS 5 DALAM MATA PELAJARAN IPAS - Bambang; Erni Suharini; Arif Widyatmoko (JISPE Journal of Islamic Primary Education, 2025)
This study aims to explore the understanding of 5th-grade students at SD Al Hikmah Surabaya regarding the concept of ecosystems in the Natural and Social Sciences (IPAS) subject. Using a descriptive qualitative approach, data were collected through classroom observations, teacher interviews, and analysis of learning documentation. The results indicate that students have a good grasp of biotic and abiotic components but struggle with more complex concepts such as food chains and nutrient cycles. Teachers employed various methods including lectures, group discussions, simple experiments, and visual media, which were effective in introducing basic ecosystem concepts. However, limited instructional time and less interactive learning media posed challenges in deepening student understanding. The learning process also positively contributed to raising students’ environmental awareness, encouraging them to care more about nature conservation. Therefore, this study recommends the use of more interactive and experience-based learning methods, including the integration of digital technology, to help students gain a more comprehensive and contextual understanding of ecosystems.